Time-resolved fluorescence resonance energy transfer-based lateral flow immunoassay using a raspberry-type europium particle and a single membrane for the detection of cardiac troponin I - Lee, Kyung Won; Kim, Ka Ram; Chun, Hyeong Jin; Jeong, Kwan Young; Hong, Dong Ki; Lee, Kook Nyung; Yoon, Hyun C. (Biosensors and Bioelectronics, 2020)
Herein, we report a novel lateral flow immunoassay (LFIA) system for detecting cardiac troponin I (cTnI) in serum using the time-resolved fluorescence resonance energy transfer (TR-FRET) technique and the fusion 5 membrane. The fusion 5 membrane is used as a strip for LFIA, and it is constructed without additional matrices (such as a sample or conjugation pad). Although this strategy for constructing the LFIA strip is quite simple and cost-effective, LFIA is still not suitable for the analysis of biomarkers that require high sensitivity, such as cTnI. Therefore, the highly sensitive TR-FRET technique is integrated with a fusion 5 membrane-based LFIA strip. To accomplish this, a microparticle covered with europium chelate-contained silica nanoparticles is synthesized as a raspberry-type particle and used as a fluorescence donor. A gold nanorod (GNR) is used as a fluorescence acceptor particle. In the TR-FRET-based LFIA system, the competitive immunoassay should be performed to satisfy the condition required for the FRET phenomenon to occur. Therefore, the fluorescence signal is proportional to the cTnI concentration, ensuring a quantitative analysis of cTnI can be accomplished by measuring the fluorescence signal between the raspberry-type europium particles and GNR. Using the developed TR-FRET-based LFIA system, sensitive detection of cTnI is successfully achieved with a limit of detection of 97 pg/mL in human serum. Moreover, because the result can be obtained using one matrix (the fusion 5 membrane), the developed LFIA system can be employed in cTnI diagnosis with a simple manufacturing process.
Keywords: Cardiac troponin I; Competitive immunoassay; Fluorescence signals; Lateral flow immunoassay; Lateral flow immunoassays (LFIA); Manufacturing process; Sensitive detection; Time-resolved fluorescence; Biosensing Techniques; Europium; Fluorescence Resonance Energy Transfer; Humans; Immunoassay; Limit of Detection; Rubus; Troponin I; Cardiac troponin I; Europium silica microparticle; Fusion 5 membrane; Lateral flow immunoassay; Time-resolved fluorescence resonance energy transfer